Short sellers' accusations against Chinese reverse mergers: Information analytics or guilt by association? - Hongqi Liu; Nan Xu; Jianming Ye (China Journal of Accounting Research, 2015)
This paper studies short sellers' trading strategies and their effects on the financial market by examining their accusations of fraud against Chinese reverse merger firms (CRMs) in the US. We find that short sellers rely on firms' fundamental information, especially relative financial indicators, to locate their 'prey.' Specifically, they compare a target firm's financial indicators (e.g., growth and receivables) with both the industry average and the firm's history. We find no evidence that short sellers accuse CRMs simply because of their reverse merger label. Additionally, we test the accuracy of short sellers' accusations in the long run and find that accused firms are more likely to delist and less likely to recover from price plunges. Our results also indicate that CRMs' high exposure to short sellers' accusations stem from adverse selection problems: firms with high litigation risk are more likely to choose reverse mergers to access the US capital market. Overall, our results support the view that short sellers are sophisticated investors and shed some light on their decision processes.
Keywords: 650; Chinese reverse mergers; Fraud accusation; Guilt by association; Information analytics; Short sellers